NU Scapes Enterprise / Felorida Ak Tambi...[et al] - Tambi, Felorida; Ricky Aran, Jascinta; Andrew Kere, Julia; Muhd Jasri, Nor Armiza Nawai (2010)
Nu Scape Enterprise is the company that will provide the best service in the designing desires exterior and interior design for our customers house.This company is build up in order to fulfill the believes on the chance of success if we open up our Nu Scape in Mukah. We realize that there are no company in Mukah that provide people in Mukah with this type of service other than us.So, we perfectly sure that this business will successfully accepted by people in Mukah.We open up this type of business and decide it to be operate in Mukah is based on many reasons. First, we realize that if we open up this type of business we do not have any competitors and this make us easy to know the suitable price that we can give to our customers, we already have our own target market, and we already decide the best marketing strategies , management strategies that will include our financial management that we know is the heart of any business and any successful strategies that will fit our Nu Scape best.We also feel that people in Mukah also must have a chance to have their ideal house concept , ideal interior decorations and suitable accessories for their house because we know that people always fit their house with unsuitable accessories ,and with our service ,we will overcome this problem and give them the best accessories for their house where they will have them with affordable price. Nu Scape will provide the best service for the customers and we guarantee that customers will satisfied ourservice.Nu Scape is form of partnership between 4 friends who study in MARA University of Technology (UiTM) in Diploma planting Industry Management. With this qualifications and knowledge, we open up this Nu Scape. The marketing is focusing on Mukah people in its division, which are Dalat, Matu and else.